Irthibậtu bayna Hifzil Qur’ận wa Natîjati Ta’allumi al-Lughah al-Arabiyah lad£ Tullậbi as-Shaffi at-Tsậmini bi Madrasah an-Namîrah al-Mutawassithah al-Islậmiyah Pekanbaru/ ارتباط بين حفظ القراۤن ونتيجة تعلّم اللغة العربية لدى الطلاب الصف الثامن بمدرسة "النمرة" المتوسطة الإسلامية باكنبارو - rahmadani, sri; karim, promadi; masrun, masrun (Al-Manar, 2024)
ABSTRAKSri Rahmadani (2024): The Relationship between Quran Memorization and the Learning Outcomes of Arabic Language for Grade Eighth Students at SMP An Namiroh Pekanbaru.This study is a quantitative research with two variables: students' Quran memorization as Variable (x) and Arabic language learning outcomes as Variable (y). The method used in this research is correlation. The objectives of this study are to determine (1) the quality of students' Quran memorization, (2) the Arabic learning scores of the students, and (3) the relationship between Quran memorization and the Arabic learning outcomes of the students. This research was conducted at SMP An Namiroh Pekanbaru. The population consists of 131 eighth-grade students, and the sample size is 67 students. The data collection method used is documentation. Based on the research results, the researcher found that 42 students had good Quran memorization scores, 5 students had very good scores, 13 students had low scores, and 2 students had very low scores. Additionally, 5 students achieved excellent scores, with a range of 26-30%. The researcher found that in Arabic language learning outcomes, there were 17 excellent students, 25 very good students, 13 good students, 5 low-scoring students, and 7 very low-scoring students. The researcher concluded that the highest Arabic learning outcome scores were from 25 students with very good information, followed by 17 students with excellent information, and lastly, 5 students with low information. Based on the correlational study conducted by the researcher, it can be concluded that there is a relationship between Quran memorization and the Arabic learning outcomes of eighth-grade students at SMP An Namiroh Pekanbaru. The correlation value between Quran memorization and Arabic learning outcomes is 0.3344, indicating a very strong relationship.Keywords: Quran Memorization, Arabic Language Learning Outcomes. ملخصسري رحمداني (2024)     : ارتباط بين حفظ القراۤن ونتيجة تعلّم اللغة العربية لدى الطلاب الصف الثامن  بمدرسة "النمرة"المتوسطة الإسلامية باكنباروهذه الرسالة هي بحث كمي بمتغيرين: حفظ القرآن كمتغير (x) ونتيجة تعلم اللغة العربية كمتغير. (y) الطريقة المستخدمة في هذه الرسالة هي الارتباط. تهدف هذه الرسالة إلى تحديد (1) كيفية حفظ الطلاب للقرآن الكريم، (2) نتيجة تعلم الطلاب للغة العربية، و (3) إرتباط بين حفظ القرآن الكريم ونتائج تعلم اللغة العربية للطلاب. أجريت هذه الرسالة في مدرسة "النمرة" المتوسطة الإسلامية باكنبارو. يتكون المجتمع من 131 طالبًا في الصف الثامن، و عيننته 67 طالبًا. الطريقة المستخدمة في جمع البيانات هي التوثيق. بناءً على نتائج البحث، وجد الباحث أن 42 طالبًا حصلوا على درجات جيدة في حفظ القرآن الكريم، و5 طلاب حصلوا على درجات جيدة جدًا، و13 طالبًا حصلوا على درجات منخفضة، و2 طالبين حصلوا على درجات منخفضة جدًا. بالإضافة إلى ذلك، حصل 5 طلاب على درجات ممتازة، بنطاق يتراوح بين 26-30%. وجدت الباحثة أن في نتائج تعلم اللغة العربية، كان هناك 17 طالبًا ممتازًا، و25 طالبًا جيدًا جدًا، و13 طالبًا جيدًا، و5 طلاب بدرجات منخفضة، و7 طلاب بدرجات منخفضة جدًا. استنتج الباحثة أن أعلى درجات نتائج تعلم اللغة العربية كانت من 25 طالبًا بمعلومات جيدة جدًا، تلاها 17 طالبًا بمعلومات ممتازة، وأخيرًا 5 طلاب بمعلومات منخفضة. بناءً على الدراسة الارتباطية التي أجراها الباحثة، يمكن الاستنتاج أن هناك إرتباط بين حفظ القرآن الكريم ونتائج تعلم اللغة العربية لطلاب الصف الثامن في مدرسة "النمرة" المتوسطة الإسلامية بكنبارو. قيمة الارتباط بين حفظ القرآن الكريم ونتائج تعلم اللغة العربية هي 0.3344، مما يشير إلى علاقة قوية جدًا.الكلمات الرئيسية: حفظ القرآن ، نتائج تعلم اللغة العربية.